Metallurgical Waste for Sustainable Agriculture: Converter Slag and Blast-Furnace Sludge Increase Oat Yield in Acidic Soils - Olga V. Zakharova; Peter A. Baranchikov; Svetlana P. Chebotaryova; Gregory V. Grigoriev; Nataliya S. Strekalova; Tatiana A. Grodetskaya; Igor N. Burmistrov; Sergey V. Volokhov; Denis V. Kuznetsov; Alexander A. Gusev (Agronomy)
The study is the first to examine the combined use of blast-furnace sludge as a source of microelements and converter slag as a soil-deoxidizing agent in oat (Avena sativa L.) cultivation in sod-podzolic soils. It has been established that blast-furnace sludge is a highly dispersed waste, which contains about 50% iron, 7% zinc, and a small amount of calcium, silicon, magnesium, aluminum, and sulfur. Hazardous components such as lead, arsenic, etc., are not detected. Converter slag comprises porous granules up to 3 mm in size, consisting mainly of calcium compounds (CaO, Ca(CO)3, CaSiO3, CaFe2O4) and a small amount of Mn, Al, and Mg trace elements. In a laboratory experiment, blast-furnace sludge increased the germination of oats by 5–10%, regardless of the addition of a deoxidizer (slag), but at the same time suppressed the growth of stem length by a maximum of 18% at 1 g∙kg−1. The addition of slag raised substrate pH and increased the index by 8% at a sludge concentration of 0.1 g∙kg−1. Root length in deoxidizer-free variants increased by 50–60% and with the addition of slag by 27–47%. Root dry mass also increased under the addition of sludge by 85–98%; however, the addition of slag reduced the indicator to the control level. In a field experiment with the combined application of waste, an increase in yield by more than 30% was shown. When soil was treated with slag and sludge, the height of plants increased by an average of 18%. It should be noted that the introduction of waste did not affect the quality of the grain. The use of slag increased the lead content in the soil, which is probably due to the sorption properties of calcium compounds in the slag, since lead was not found in the analyzed waste. Presumably, lead is sorbed by slag from the lower soil horizons, concentrating and immobilizing it in the upper layer. This version is supported by the absence of lead accumulation in straw and oat grain. The zinc-containing sludge increased the content of this element by 33% in the soil, as well as by 6% in straw and by 14% in grain. Thus, we found that the studied metallurgical wastes can be used as nutrients for agriculture, both individually and jointly. Overall, the proposed approach will contribute both to reducing the amount of accumulated waste and to improving the efficiency and sustainability of agricultural production and CO2 sequestration. However, the features of the accumulation of heavy metals in soil and plants under the influence of the analyzed types of waste require more in-depth study, including within the framework of long-term field experiments.